The influence of capital intensity, inventory intensity, and sales growth on tax aggressiveness in manufacturing companies - Ledy Setiawati; Falensya Lucia Tanggreini (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to examine the effect of capital intensity, inventory intensity, and sales growth on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. In determining the sample, this study uses the purposive sampling method obtained from 28 companies with a total of 112 samples. This type of research is quantitative with secondary data obtained from the official website of the Indonesia Stock Exchange and the company’s official website. The analysis tool used is the Statistical Package for the Social Sciences (SPSS) version 25. The results of this study show that capital intensity and inventory intensity do not have a significant effect on tax aggressiveness. Sales growth has a negative and significant effect on tax aggressiveness.